If You Can't Include Them, Exclude Them: Countering the Arab Uprisings in Algeria and Jordan - Maria Josua (German Institute of Global and Area Studies (GIGA), 2016)
In those authoritarian regimes that remained resilient throughout the Arab uprisings, the ruling elites have maintained their power through protest management strategies designed to include or, more frequently, exclude certain societal groups. This paper compares the strategies and their respective target groups in Algeria and Jordan, two cases of limited protests despite which authoritarianism has remained resilient. In both countries, inclusionary strategies towards protesters were pursued only half-heartedly. When they failed, they were subsequently replaced by exclusionary mechanisms. More successful inclusionary strategies were aimed at another target, the regime's support base. The decreasing extent of political protests can thus hardly be attributed to responsive elite behaviour. The limited use but credible threat of repression together with discourses of deterrence prevented greater mobilisation, partly by invoking negative examples of the past or neighbouring countries. However, the massive reliance on exclusionary mechanisms calls the future stability of the Arab world into question.
Keywords: 300; inclusion; exclusion; Arab uprisings; protests; repression; state-society relations